177Lu-DOTATATE peptide receptor radionuclide therapy in patients with borderline low and discordant renal parameters: Treatment feasibility assessment by sequential estimation of triple parameters and filtration fraction - Naik, Chinna; Basu, Sandip (World Journal of Nuclear Medicine, 2018)
The aim was to assess the effect of standard fixed-dose protocol of 177Lu-DOTATATE peptide receptor radionuclide therapy (PRRT) in patients with borderline low renal function of one parameter (glomerular filtration rate [GFR], effective renal plasma flow [ERPF] or serum creatinine), that was discordant with the remaining parameters and determine the feasibility of this procedure in this group of patients. Renal toxicity of PRRT is a routine issue or concern for such cases. We compared different renal parameters used for pretherapy assessment in patients with borderline low single parameter at baseline and their potential significance with regards to deterioration of renal function subsequently. A retrospective analysis was performed in patients of metastatic neuroendocrine tumors who received therapeutic 177Lu-DOTATATE (using standard fixed-dose protocol) and had borderline compromised renal parameter values (either of GFR/ERPF/serum creatinine). Filtration fraction (FF) was also estimated in each case and all renal parameters were correlated using kappa statistics. The characteristics of cases showing progressive worsening of renal function in the follow-ups were also studied. A total of 15 patients (11 males, 4 females; age range: 32–75 years) were selected among a population of 450 patients. The follow-up duration ranged from 10 to 48 months and administered cumulative activity ranged 9.9–31.3 GBq (2–5 cycles). Based on the parameter characteristics, the study population was divided into following four groups: (a) patients with reduced GFR and maintained ERPF and normal serum creatinine (n = 3); (b) patients with reduced ERPF with maintained GFR and borderline elevated/normal serum creatinine (n = 3); (c) patients with both reduced GFR and ERPF and maintained serum creatinine (n = 1); (d) patients with compromised single kidney function (n = 5). A total of four patients were found who had normal baseline renal function values but showed progressive worsening in the subsequent period. There was no significant change in renal parameters during the follow-up in both Groups a and c. Two patients of Group b demonstrated well-maintained other renal parameters, whereas in 1 patient, there was the evidence of renal toxicity with gradual fall of GFR and ERPF and progressive increase in serum creatinine level. In patients with compromised single kidney function at baseline (Group d), there was overall maintained normal renal parameters, whereas 3 of 5 (60%) showed the increase of FF of the affected kidney. Interestingly, a compensatory hyperfunction was noted in the contralateral kidney. PRRT with 177Lu-DOTATATE is feasible and can be considered in patients with reduced GFR and with maintained ERPF and normal serum creatinine and also in the presence of single compromised parameter if the other two are normal; however, these patients need critical monitoring.
Keywords: 177Lu-DOTATATE; effective renal plasma flow; glomerular filtration rate; neuroendocrine tumor; peptide receptor radionuclide therapy; serum creatinine